Factors influencing dietary patterns among the youth from higher educational institutions in India - Soam, Sudhir K.; Yashavanth, B. S.; Dhumantarao, Thammi Raju; Maruthamuthu, Balakrishnan; Balasani, Raghupathi; Rakesh, S. (Frontiers in Nutrition, 2023)
Purpose To determine the factors influencing the dietary habits of the varied groups among adults in India Design/approach Data on food habits such as choice of diet, preference towards meat, spicy food, sugar/calorie etc., were collected from the participants (from several higher education institutions) of different training programmes and events organised at ICAR-NAARM, Hyderabad and its students of Post Graduate Diploma in Agribusiness Management. Findings Results of the study indicated that the food choice of the respondents is highly influenced by their region, age and gender. Most of the respondents preferred vegetarian food with increasing age. It is suggested from the research that the food menu should be prepared based on the region, age, and gender of the consumer in any food serving institution. Novelty Analysis of dietary patterns can be helpful for doctors, dieticians, food policy-making, restaurateurs, youth hostels, food organisations, mega kitchens etc. that would contribute to responsible food consumption.